2020
DOI: 10.1183/23120541.00583-2020
|View full text |Cite
|
Sign up to set email alerts
|

CXCL-8-dependent and -independent neutrophil activation in COPD: experiences from a pilot study of the CXCR2 antagonist danirixin

Abstract: Neutrophils are central to the pathophysiology of COPD, yet there are no licensed therapies directly targeting neutrophil-mediated inflammation [1]. Neutrophils are recruited to the COPD airway via chemoattractants such as interleukin-8 (CXCL-8) and are activated by pro-inflammatory cytokines abundant in inflamed airways [2]. Following activation, neutrophils can degranulate, releasing damaging proteases and mediators, or can form neutrophil extracellular traps (NETs), which consist of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
(19 reference statements)
0
22
0
Order By: Relevance
“… 134 However, further investigation of this drug demonstrated an increase in the incidence of exacerbations in patients with chronic mucus secretion. 135 These observations have now led to the suggestion that such therapies targeting neutrophils will be of benefit in a subset of patients, 136 but identification of these is not clear.…”
Section: Implications For Therapymentioning
confidence: 99%
“… 134 However, further investigation of this drug demonstrated an increase in the incidence of exacerbations in patients with chronic mucus secretion. 135 These observations have now led to the suggestion that such therapies targeting neutrophils will be of benefit in a subset of patients, 136 but identification of these is not clear.…”
Section: Implications For Therapymentioning
confidence: 99%
“… 42 Keir et al demonstrated that there was a subset of individuals with COPD in whom neutrophil activation was independent of CXCR2. 43 Another study found that specific CXC chemokines resulted in enhanced migration of PBMCs/monocytes from patients with COPD, which was mediated via CXCR1 and CXCR2. 44 CXCR2 was significantly increased in patients with severe/very severe COPD compared with patients with mild/moderate COPD and control healthy smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind RCT (NCT03250689) [ 16 ], participants were randomised (3:1) to receive danirixin 35 mg twice daily or placebo for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted pilot RCT primarily to study the effects of a CXCR2 antagonist, danirixin, the primary results for which have been published [ 16 ]. In this pilot RCT, our exploratory objectives were feasibility of measuring VOCs via multiple techniques, assessing relationships between VOCs and Haemophilus colonisation, and whether CXCR2 antagonism with danirixin altered lung microbiome composition in individuals with COPD.…”
Section: Introductionmentioning
confidence: 99%